Decreased tumour necrosis factor-α production by monocytes of granulomatosis with polyangiitis. (October 2014) - Park, JK; Lee, EB; Song, YW
<x xml:space="preserve">Abstract</x> Objectives: We hypothesized that monocytes in patients with granulomatosis with polyangiitis (GPA) are polarized towards alternative activation with decreased tumour necrosis factor (TNF)-α production and that tissue-infiltrating monocytes/macrophages in granulomatous GPA lesions express CD163, a marker of alternative macrophage activation. Method: CD16+ monocytes in peripheral blood mononuclear cells (PBMCs) were quantified by flow cytometry. Monocytes were stimulated with increasing concentrations of lipopolysaccharide (LPS), and TNF-α production was measured at 4 and 24 h. CD163 expression in lung biopsies of patients with GPA was detected by immunohistochemistry. Results: Circulating CD16+ monocytes were more frequent in GPA patients compared to controls (4.7 ± 2.8% vs. 1.9 ± 1.2%, p < 0.001). Upon activation with LPS, TNF-α production did not differ between CD16+ and CD16– monocytes. Stimulated monocytes from GPA patients produced significantly less TNF-α compared with monocytes from healthy controls (2903 ± 1320 pg/mL vs. 8335 ± 4569 pg/mL, p < 0.001). Macrophages expressing CD163 were enriched in granulomatous lung lesions of GPA patients. Conclusions: Decreased TNF-α production by circulating monocytes and CD163 overexpression by tissue monocytes/macrophages in granulomatous pulmonary lesions may suggest that monocytes/macrophages are alternatively activated in GPA.